Effects of Various Steam Explosions on the Efficiency, Yield, and Loss in a Hydraulic Press Extractor of Fruit Juice - Oduntan, Oluwafemi Babatunde; Bankole, Bankole; Oluwatosin, Ruth; Bamgboye, Adeleke Isaac; Oduntan, Abosede Oluwakemi (Universitas Brawijaya, 2024)
High post-harvest losses occur as a result of the fruits rapid decline in quality after harvest. Using a steam exploded simple juicer is one approach to make up for this loss. The aim of this study was to optimise the processing conditions of a manually operated hydraulic press for the extraction of fruit juice. To measure extraction yield, efficiency, and principle extraction loss, freshly selected fruits (orange, pineapple, and watermelon) were sliced to 20, 40, 60, and 80 mm, steam-conditioned for varying lengths of time (5, 10, and 15 minutes), and loaded onto the machine at various rates (50, 75, and 100%). The Response Surface Methodology (RSM) was employed to optimize the procedure. To ascertain the variations in extraction yields using reference extraction methods, a comparative study was also carried out. The impact of the investigated parameters on the extraction procedures were significant (p 0.05). The pineapple was sliced to 71.25 mm, steamed for 12.60 minutes, and loaded at a rate of 50.61% under the optimal conditions of the press, resulting in an extraction yield, machine efficiency, and extraction loss, which were 79.56, 67.48, and 11.96% respectively. When compared to reference extraction methods, the device yielded the highest fruit extraction yields. Thus, the press was an efficient, effective, and industrially appropriate extraction method that minimizes post-harvest losses.